The detrimental effects of student-disordered behavior at school: evidence from using the cusp catastrophe - Alkhadim, Ghadah (Frontiers in Psychology, 2024)
The purpose of the present study is to examineelucidate the potentially complex relationship between disordered behavior at school and students' engagement with reading activities given that they enjoy reading. Of particular interest is the role of disordered behavior which we believe moderated the relationship between liking reading and reading engagement. Participants were 2,420 fourth graders who participated in the 2021 PIRLS study from Saudi Arabia and were selected using stratified random sampling from 117 schools in the Kingdom. Data were analyzed using linear and non-linear means such as the linear model, the logistic model, and the cusp catastrophe. Results pointed to the superiority of the cusp catastrophe towards predicting student engagement in reading by highlighting the splitting role of students' disruptive classroom behavior. It was evident that exceeding a critical upward level in disruptive classroom behavior was associated with unpredictable and sudden changes in reading engagement. It is concluded that the application of non-linear means may be conducive to understanding complex educational phenomena.